2016
DOI: 10.3390/ma9100813
|View full text |Cite
|
Sign up to set email alerts
|

An Experimental and Theoretical Investigation of the Electronic Structures and Photoelectrical Properties of Ethyl Red and Carminic Acid for DSSC Application

Abstract: The photoelectrical properties of two dyes—ethyl red and carminic acid—as sensitizers of dye-sensitized solar cells were investigated in experiments herein described. In order to reveal the reason for the difference between the photoelectrical properties of the two dyes, the ground state and excited state properties of the dyes before and after adsorbed on TiO2 were calculated via density functional theory (DFT) and time-dependent DFT (TDDFT). The key parameters including the light harvesting efficiency (LHE),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
42
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 75 publications
(48 citation statements)
references
References 86 publications
4
42
0
2
Order By: Relevance
“…However, the dye‐3 is relatively more reactive and has greater charge transfer ability which points to its better photo to electric conversion efficiency. The chemical reactivity of a molecule indicates tendency to stabilize by attracting charge from environment . It has already been found that for the efficient solar energy harvesting the most favorable energy gap should be between 1.1 eV to 2 eV .…”
Section: Resultsmentioning
confidence: 99%
“…However, the dye‐3 is relatively more reactive and has greater charge transfer ability which points to its better photo to electric conversion efficiency. The chemical reactivity of a molecule indicates tendency to stabilize by attracting charge from environment . It has already been found that for the efficient solar energy harvesting the most favorable energy gap should be between 1.1 eV to 2 eV .…”
Section: Resultsmentioning
confidence: 99%
“…and Li et al. . The configurations of the dye/TiO 2 complexes were optimized via DFT//B3LYP/6‐31G(d) for C, H, O, N, Se atoms and effective core potential (ECP) LANL2DZ and the accompanying basis set for Ti atom.…”
Section: Methodsmentioning
confidence: 99%
“…Masa hidup tereksitasi normal, dan pada saat yang sama, parameter reaktivitas kimia menggambarkan reaktifitas yang lebih rendah dan lebih tinggi daya penerimaan elektron dari asam carminat namun memiliki pengaruh pada hubungan arus yang singkat. Oleh karena itu, asam carminat menunjukkan efisiensi konversi fotolistrik yang (Sun et al, 2016). Penggunaan asam sitrat dimungkinkan kurang tepat pada saat ekstraksi antosianin Setelah pengamatan hari ke-5, SSPT menghasilkan tegangan listrik yang memiliki kecenderungan menurun.…”
Section: Pengujian Kemampuan Sspt Dalam Menghasilkan Listrikunclassified